2000
DOI: 10.1243/0954407001527484
|View full text |Cite
|
Sign up to set email alerts
|

The automotive connector: The influence of powering and lubricating a fretting contact interface

Abstract: The increasing amount of telematic and other electronic systems in the modern motor vehicle demands higher performance and reliability in ever decreasing space. Over many years, connector technology has advanced but is still regarded as the weak link in the reliability chain. Fretting corrosion is thought to be the main failure mechanism causing intermittent high contact resistance.A low-frequency fretting apparatus is used in this study to induce fretting corrosion on contact samples. Low frequency is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Hence, it is evident that lubricant used in the present study is very effective in delaying the fretting wear during the initial stages and in preventing the oxidation and, accumulation of oxidation products at the contact zone in the later stages. Reduced wear due to decreased metal-metal contact and retardation of surface oxidation for lubricated contacts has also been observed earlier many authors (Antler, 1985;Abbott, 1996;Swingler, 2000). The observations of the surface analytical studies and the observed changes in the contact resistance of lubricated tin plated contacts ( Figure 3) correlate very well.…”
Section: Surface Characteristics Of the Contact Zone Of Lubricated Cosupporting
confidence: 83%
See 2 more Smart Citations
“…Hence, it is evident that lubricant used in the present study is very effective in delaying the fretting wear during the initial stages and in preventing the oxidation and, accumulation of oxidation products at the contact zone in the later stages. Reduced wear due to decreased metal-metal contact and retardation of surface oxidation for lubricated contacts has also been observed earlier many authors (Antler, 1985;Abbott, 1996;Swingler, 2000). The observations of the surface analytical studies and the observed changes in the contact resistance of lubricated tin plated contacts ( Figure 3) correlate very well.…”
Section: Surface Characteristics Of the Contact Zone Of Lubricated Cosupporting
confidence: 83%
“…Lubrication has also been shown to reduce or eliminate fretting corrosion (Swingler, 2000) and is considered as a possible solution for preventing fretting corrosion (van Dijk and van Meijl, 1999). A variety of lubricants, namely, polyphenyl ethers, natural and synthetic hydrocarbons, several types of esters, polyglycols, some fluorinated materials, silicone and some proprietary formulations were evaluated for their suitability for connector applications (Freitag, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such manifestations fracture the solder contacts and instigate intermittent faults. Electrical intermittency is also caused by contact fretting [15,20]. Fretting corrosion occur particularly in tin plated contacts, as a degradation mechanism caused by the presence of humidity which oxidizes the metal-metal interface.…”
Section: Printed Circuit Board Interconnectorsmentioning
confidence: 99%
“…It should not be too big lest the area should lose its planovertical nature and in order to avoid a decrease in its bearing capacity beyond the allowable limit. It follows from different investigations that (a lot depends on the contour of a particular friction spot) the coverage degree, while the necessary load-bearing capacity is ensured, should not be greater than 25-48% (Swingler, 2000) as its increase does not considerably improve lubrication and may even cause the above mentioned negative effects reflected by increased wear.…”
Section: Introductionmentioning
confidence: 99%